The Empowering Church Members in the Implementation of the Creative Economy: An Interpretative Approach to the Concept of Missionary Congregation Development - Sarah Martha Juliana; Pantjar Simatupang (Asian Journal of Management, Entrepreneurship and Social Science, 2023)
The big dream together towards a Golden Indonesia in 2045 is a common dream as the Indonesian people, this big dream should be the target of the church's call and mission because the Church is part of the community in this country. Together with the World Council of Churches, we always encourage the Churches to carry out their mission to fulfill the Great Commission and play a role in the world. Of course, this is a serious matter to study. The formation of church members enables the congregation and society to become God's co-workers. The focus of this research is on the church institution, namely Gereja Protestan di Indonesia Bagian Barat (GPIB), which seeks to revive two church functions, namely the main function of the Church and the supporting function of the Church. The aim is that the mission role of the church can be optimally pursued for the church and its impact on society. How can this struggle be overcome by reviewing the study of Maotimoe's basic thoughts on the Development of Missionary Congregations, the GPIB documents so that they can become a solution to carrying out the GPIB mission. In writing this article the author used the library research method. The author read several supporting sources and several Church documents as the main source of this research. Then these findings will become recommendations for implementing the church's mission between Maitimoe's thoughts and Indonesia's hopes towards a Golden Indonesia 2045 so that the Church is not essentially for itself but for the world and the limitations of studies on theological concepts and Church Economic Development Keywords: Missionary Church Congregation, Empowering Church Member, Creative Economy